Réponses

2014-09-20T22:14:53+02:00
Bonsoir
1)
A(x) = (x-4)(5x+4)-(6x-3)² = 5x² + 4x - 20x - 16 + 36x² + 36x - 9
A(x) = 41x² + 16x - 25 

B(x) = (x-3)(x+3) - 4(2x+1)(x-3) = x² - 9 - 4(2x² - 6x + x - 3)
B(x) = -7x² + 24x + 3 

C(x) = (3/2)x(4/5 - 2x/3) 
C = (12/10)x - (3/2)(2/3)x² = (6/5)x - x² 
2)
D(x) = (3-4x)(4x+1-2x-1) = (3-4x)(2x)

E(x) = (-3x-1)(x+6+1) = (-3x-1)(x+7)

F(x) = (5x-9)(5x-9-x-1) = (5x-9)(4x-10)
3)
G(x) = (2x-7-7)(2x-7+7) = (2x -14)(2x)

H(x) = (5x-8-2x-9)(5x-8+2x+9)
H(x) = (3x-17)(7x+1)
Bonne soirée